Reservoir computing and decision making using laser dynamics for photonic accelerator. (12th March 2020) - Uchida, Atsushi; Kanno, Kazutaka; Sunada, Satoshi; Naruse, Makoto
Abstract: The photonic accelerator is a new paradigm of photonic technologies for artificial intelligence, wherein the systems can accelerate information processing in electronic computing. Schemes for reservoir computing and decision making are promising examples of the photonic accelerator. In this work, we describe recent advances in the architectures of reservoir computing and decision making based on complex photonics, wherein the physics of light, including ultrafast dynamics in semiconductor lasers with optical feedback, plays a crucial role in the photonic accelerator.